Penerapan Model Pembelajaran Kooperatif Tipe TAI untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 2 Lubuk Alung - NADITA LERIAN ROSENDRA (Departemen Matematika, 2019)
The mathematical concept understanding is one of the goals of mathematics learning that must be achieved by students through the process of learning mathematics. It is also basic of the other mathematical skills. But in fact learning activities in schools are not optimal in facilitating students to improve the mathematical concept understanding. One effort to overcome this problem is to apply the Team Assisted Individualization (TAI) model. The purpose of this study is to describe whether the mathematical concept understanding of students who learn by using the TAI model are better than students who learn with direct learning. This type of research is quasi-experimental with the Static Group Design research design. Based on the results of data analysis, it was concluded that the mathematical concept understanding of students who learn to use the TAI model are better than students who learn with direct learning in class VIII SMPN 2 Lubuk Alung. Keywords – Mathematical Concept Understanding, Team Assisted Individualization Model, Direct Learning